Medicinal plant extracts on the control of Diabrotica speciosa (Coleoptera: Chrysomelidae) Extratos de plantas medicinais no controle de Diabrotica speciosa (Coleoptera: Chrysomelidae) - F.S. Barbosa; G.L.D. Leite; E.R. Martins; V.A. D'avila; V.M Cerqueira (Universidade Estadual Paulista, 2013)
The aim of this study was to evaluate the insecticidal effect of aqueous, alcoholic, and oil extracts from leaves of eight medicinal plants against Diabrotica speciosa prepared at five concentrations. The extracts that used commercial soybean oil as solvent showed the highest D. speciosa mortality due to the solvent itself, regardless of the used plants and their concentrations. Thus, commercial soybean oil was discarded as solvent since at these volumes it would cause serious phytotoxicity problems. After 24 hours of exposure of the pest to the extracts, the highest D. speciosa mortality values were observed for Copaifera langsdorfii and Chenopodium ambrosioides extracts, both in 5% alcohol, and Artemisia verlotorum, in 10% water. However, in the last mortality assessment (48 h), C. langsdorfii extract in 5% alcohol showed higher mortality of this pest, followed by C. ambrosioides extract in 5% alcohol, compared to the remaining plants. O objetivo deste trabalho foi avaliar o efeito inseticida de extratos aquosos, alcoólicos e oleosos de folhas de oito plantas medicinais contra Diabrotica speciosa preparadas em cinco concentrações. Os extratos que utilizaram óleo de soja comercial como solvente apresentaram as maiores mortalidades de D. speciosa em função do próprio óleo, independentemente das plantas utilizadas em suas concentrações. Sendo assim, o óleo de soja comercial foi descartado como solvente, pois nestes volumes acarretaria sérios problemas de fitotoxidade. Após 24 horas de exposição da praga aos extratos, os maiores valores de mortalidade de D. speciosa foram observados nos extratos de Copaifera Langsdorfii e de Chenopodium ambrosioides, ambos em álcool 5%, e de Artemisia verlotorum, em água 10%. Entretanto, na última avaliação de mortalidade (48 h), o extrato de C. langsdorfii em álcool a 5% apresentou maior mortalidade dessa praga, seguida pelo extrato alcoólico a 5% de C. ambrosioides comparada às demais plantas.